Isotope-geochronological (U-Th-Pb, Lu-Hf) study of the zircons from the Archean magmatic and metasedimentary rocks of the Podolia domain, Ukrainian Shield. - Bibikova, Elena V; Claesson, S; Fedotova, A A; Stepanyuk, L M; Shumlyansky, L V; Kirnozova, Tatyana I; Fugzan, Mira M; Il'insky, L S (PANGAEA, 2013)
Zircons from the oldest magmatic and metasedimentary rocks in the Podolia domain of the Ukrainian shield were studied and dated by the U-Pb method on a NORDSIM secondary-ion mass spectrometer. Age of zircon cores in enderbite gneisses sampled in the Kazachii Yar and Odessa quarries on the opposite banks of the Yuzhnyi Bug River reaches 3790 Ma. Cores of terrigenous zircons in quartzites from the Odessa quarry as well as in garnet gneisses from the Zaval'e graphite quarry have age within 3650-3750 Ma. Zircon rims record two metamorphic events around 2750-2850 Ma and 1900-2000 Ma. Extremely low U content in zircons of the second age group indicates conditions of the granulite facies metamorphism in Paleoproterozoic within the Podolia domain. Measured data on orthorocks (enderbite-gneiss) and metasedimentary rocks unambiguously suggest existence of the ancient Paleoarchean crust in the Podolia (Dniester-Bug) domain of the Ukrainian shield. They contribute in our knowledge of scales of formation and geochemical features of the primordial crust.
Chemical and isotopic compositions of Archean magmatic and metasedimentary rocks and minerals from the Podolia domain, Ukrainian Shield
Keywords: Archive of Ocean Data; ARCOD